(untitled) (American Journal of Islam and Society, 2013)
We have come to expect nothing but bad news about Afghanistan, nothing but negative prognoses of that troubled state from policymakers, pundits, and journalists. Only rarely do we hear what scholars of Afghan studies have to say. In Beyond the “Wild Tribes”: Understanding Modern Afghanistan and Its Diaspora, the country and its people are presented in a far more complicated fashion than the usual this-place-is-doomed mantra. Contributions include a review and critique of research methodologies in Afghanistan and the diaspora, the role of gender in community-based justice, models of national and local governance, the refugee warrior, and migration. There is much to like about this book, and even those knowledgeable about the complex problems plaguing the fledgling state will learn something ...